A 10-year review of periconceptual folic acid supplementation in women with epilepsy taking antiseizure medications - Ciara Turner; Trudi McIntosh; Damon Gaffney; Mark Germaine; Jennifer Hogan; Amy O’Higgins (The Journal of Maternal-Fetal & Neonatal Medicine, 2025)
Background Epidemiological studies have reported that women with epilepsy who are taking antiseizure medications have an increased risk of Neural Tube Defects. Periconceptual folic acid supplementation potentially prevents two-thirds of cases. International guidelines recommend that women at increased risk of a pregnancy complicated by a Neural Tube Defect who could become pregnant should start high-dose (5 mg daily) oral folic acid at least three months before conceiving. The purpose of the study was to examine supplementation in women taking antiseizure medications who delivered a baby weighing >499 g during the ten years 2013–2022 in a large maternity hospital.Methods The hospital’s computerized database contains standardized maternal clinical and sociodemographic details which were entered at the first antenatal visit in the obstetric records. The data on all women with epilepsy taking antiseizure medications was anonymized before coding.Results In the ten years, 75,869 women delivered a baby weighing >499 g. Of the deliveries, 632 (0.83%) were to women with epilepsy. Of these, 250 (0.33%) were taking antiseizure medications when they presented for antenatal care. The most frequently prescribed medications were lamotrigine n = 98 (33.8%) and levetiracetam n = 89 (30.7%). Monotherapy was prescribed in 211 (84.4%) women and polytherapy in 39 (15.6%). Three (1.2%) women took no folic acid before or after conception and 59 (23.6%) only took it after conception. Of the 188 (75.2%) who took folic acid before conception, 164 (65.6%) took high-dose 5 mg and 24 (9.6%) took low-dose 0.4 mg. No maternal characteristics were associated with taking high-dose folic acid before conception. Compliance with the national guidelines in the 16 women taking valproate was 30.8% compared with 76.0% for the other 234 women taking medications (p < 0.03). Compliance in the 211 women receiving monotherapy was 72.5% compared with 25.6% in the 39 women receiving polytherapy (p < 0.03).Conclusions Two-thirds of women taking antiseizure medications complied with national guidelines on high-dose periconceptual folic acid supplementation. A particular concern is the suboptimal compliance in women prescribed valproate and polytherapy, which are two cohorts at higher risk of a neural tube defect. These findings need to be communicated to women with epilepsy in their reproductive years and their doctors.Key points Of 75,869 women delivered over 10 years, 250 (0.33%) were on medications for epilepsy at presentation34.4% of women taking medications did not start high dose folic acid before conception23.6% of women did not start folic acid until after conceptionCompliance with recommendations was lowest in women prescribed valproate or polytherapyNo maternal characteristics were identified which were associated with suboptimal compliance